2018
DOI: 10.1080/00365521.2018.1435717
|View full text |Cite
|
Sign up to set email alerts
|

Does a histologically inflamed resection margin increase postoperative complications in patients with Crohn’s disease?

Abstract: After bowel-sparing surgery for CD, the frequency of histologically inflamed resection margins is high. However, postoperative complication rate remains low. The current practice with resection of only the most affected bowel segments for CD seems to be a safe choice. We still need further research concerning risk factors for postoperative complications in Crohn's patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…While the mean time from surgery to recurrence was comparable between both groups (4.5 versus 4.4 years), 75.5% of patients with a positive resection margin suffered from recurrence compared to 69.9% without microscopic inflammation (p = 0.57) [84]. Furthermore, in a single center study from Finland no significant differences were seen regarding the postoperative rates of disease recurrence in case of active inflammation at the resection margin [76]. Since the goal of CD surgery is usually a limited bowel resection to avoid short-bowl syndrome, extended resections are not supported based on the available evidence to date.…”
Section: Improved Surgical Technique May Further Support the Beneficial Effects Of Surgery To Maintain Remission In CDmentioning
confidence: 84%
See 1 more Smart Citation
“…While the mean time from surgery to recurrence was comparable between both groups (4.5 versus 4.4 years), 75.5% of patients with a positive resection margin suffered from recurrence compared to 69.9% without microscopic inflammation (p = 0.57) [84]. Furthermore, in a single center study from Finland no significant differences were seen regarding the postoperative rates of disease recurrence in case of active inflammation at the resection margin [76]. Since the goal of CD surgery is usually a limited bowel resection to avoid short-bowl syndrome, extended resections are not supported based on the available evidence to date.…”
Section: Improved Surgical Technique May Further Support the Beneficial Effects Of Surgery To Maintain Remission In CDmentioning
confidence: 84%
“…Regarding anastomotic leakage, Garofalo et al reported that a positive proximal resection margin is associated with increased rates of anastomotic leakage postoperatively in comparison to patients without microscopic involvement of inflammatory cells of the anastomosis [74]. However, Schineis et al and Aaltonen et al reported in single center studies that no differences regarding anastomotic leakages were seen following microscopic inflammation, and that overall postoperative complications rates were low [75,76]. Similarly, analyzing our own cohort we did not see increased rates of anastomotic leakages for patients with positive resection margins following ileocecal resection (data not published yet).…”
Section: Improved Surgical Technique May Further Support the Beneficial Effects Of Surgery To Maintain Remission In CDmentioning
confidence: 99%
“…Furthermore, another relevant and well-discussed issue is the effect of the positive resection margins on the rates of postoperative disease recurrence [ 10 ]. The current evidence is heterogenous on the question of whether a positive resection margin results in a higher risk of disease recurrence [ 29 , 30 , 31 ]. While the current guidelines do not recommend inflammation-free margins due to the lack of robust evidence and the importance of bowel-sparing resections, future strategies could focus on the relevance of intraoperative diagnostics to avoid positive resection margins, as this is the state-of-the-art approach in surgical oncology.…”
Section: Discussionmentioning
confidence: 99%
“…From 1945 citations, 23 studies (15 retrospective cohorts and 8 prospective cohorts) were included with a total of 7147 patients [32, 46–68]. Study and patient characteristics are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%